Effect of a fat-free diet and of different dietary fatty acids (palmitate, oleate, and linoleate) on the fatty acid composition of fresh-water fish lipids - Brenner, Rodolfo Roberto (1963)
When fresh-water fish Pimelodus maculatus were fed a fat-deficient diet, the concentration of linoleic and arachidonic acids in glycerides and phospholipids decreased, and the concentration of palmitic, palmitoleic, oleic, and eicosatrienoic acids increased. When fat-deficient, fresh-water fish Parapimelodus valenciennesi were fed a diet containing methyl palmitate, methyl oleate, and methyl linoleate, palmitic and oleic acid seemed to be stored mainly in the glycerides, whereas linoleic acid was deposited in both glycerides and phospholipids. Some linoleic acid was transformed into arachidonic. The concentration of palmitic acid in fish lipids was very well regulated by the animal.